THE STUDY ON THE EFFECT OF GENDER ON SERUM BILIRUBIN CONCENTRATION IN INFANTS WITH NEONATAL HYPERBILIRUBINEMIA - DR. D.V. KRISHNA VENI (International Journal of Pharma and Bio Sciences, 2013)
The study was undertaken to observe the gender based variation in serum bilirubin levels in neonatal Hyperbilirubinemia. A total of seventy nine healthy full term infants (50 females and 29 males) in age group of 1-7 days, who presented with visible non-hemolytic hyperbilirubinemia were analyzed. There was no significant difference in maternal age, gestational age, birth weight and perinatal age in between male and female infants. Total bilirubin levels were high both in female and male infants and there was no significant difference between them. But the direct bilirubin levels were significantly high in female infants compared to male infants during the neonatal period.